Metabolic pathway engineering for enhanced biohydrogen production - Mathews, J.; Wang, G.
Hydrogen is an ideal, clean, and potentially sustainable energy carrier for the future due to its abundance and non-polluting nature. Numerous bacteria, cyanobacteria, and algae are capable of producing hydrogen from water, solar energy, and a variety of organic substrates. Improvement of these diverse biochemical pathways is needed in order to make biohydrogen competitive with current production methods. This review summarizes some of the main biological pathways that produce hydrogen and their limiting factors. It also describes how metabolic engineering strategies are being used to overcome these limitations, increase yields, and broaden substrate utilization.
Keywords: PATHWAY ENGINEERING; METABOLIC ENGINEERING; BIOHYDROGEN PRODUCTION